Effect of land use on carbon-, nitrogen- and silica soil stocks in the South African bushveld - Bal, K. D.; Louw, V.; Struyf, E.; Sara, J. R.; Le Roux, J.; Ayisi, K. K.; Schoelynck, J. (Frontiers in Environmental Science, 2023)
Anthropologic land use alters soil properties and influences biological transformations in the root zone, thereby affecting the distribution and supply of soil nutrients. It is generally acknowledged that human land-use activities such as intensive cattle farming and cultivation of citrus products lead to a homogenization of soil nutrients. This research aims at investigating the heterogeneity in soil nutrient stocks and BSi stocks (a beneficial plant element) within the Savannah biome of South Africa. In this study, C-N-Si stocks and their ratios were quantified in the soil of five different land use types, common in South Africa. The five different land use types are (i) bush savannahs, (ii) mopane-dominated woodlands, (iii) annually burned land, (iv) communal grazing land and (v) citrus orchards. Empirical research however could not fully validate this hypothesis. In particular fire management and game farming (natural land use type) led to more variability in nutrient pools, with occasional occurrences of C-N-Si hotspots. Our results suggest that when ecosystem analysis of soil nutrient and carbon stocks is handled as a homogeneous unit potentially large mistakes are made, even in anthropogenic landscapes previously hypothesized with uniform nutrient distributions.